2021
DOI: 10.1080/23311975.2021.1980248
|View full text |Cite
|
Sign up to set email alerts
|

The role of user adaptation and trust in understanding continuance intention towards mobile shopping: An extended expectation-confirmation model

Abstract: With the rapid growth and intense competition of the mobile commerce market, mobile vendors consider retaining current users and facilitating them to continue shopping as vital to sustain profitability and development. This study investigates the influence of trust and perceived usefulness on continuance intention to use mobile shopping, mediated by user adaptation. This study was based on an extended expectation-confirmation model (ECM) by incorporating trust and user adaptation. A questionnaire-based survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 93 publications
(177 reference statements)
2
20
0
Order By: Relevance
“…Further, in the H4 of the study, the researchers hypothesized a significant impact of Perceived Behavioral Control on the Expectation Confirmation of the Siri users [85]. However, this impact remained insignificant, indicating inconsistency with the existing literature [44], [47]. On the other hand, the impact of Expectation Confirmation to Use Siri remained significant, with the p-value at p> 0.000.…”
Section: Ipma Discussion On Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Further, in the H4 of the study, the researchers hypothesized a significant impact of Perceived Behavioral Control on the Expectation Confirmation of the Siri users [85]. However, this impact remained insignificant, indicating inconsistency with the existing literature [44], [47]. On the other hand, the impact of Expectation Confirmation to Use Siri remained significant, with the p-value at p> 0.000.…”
Section: Ipma Discussion On Resultsmentioning
confidence: 85%
“…According to [44], expectation confirmation can also be described as realizing that the expected outcomes will be according to users' requirements. Existing research on technology and expectation confirmation found strong impacts of one's behavior on expectation confirmation [45].…”
Section: Perceived Behavior Control and Expectation Confirmationmentioning
confidence: 99%
“…Nguyen & Ha (2021) also finds that perceived usefulness is significantly associated with trust. Nguyen & Ha (2021) study stated that trust is one most important factors influencing e-commerce use. That is why customers' perceived usefulness can influence trust, which impacts the intention to use e-commerce.…”
Section: Discussionmentioning
confidence: 87%
“…Thus, it reduces information asymmetry and uncertainty and makes customers believe the product is of good quality (Yang et al, 2019). Nguyen & Ha (2021) also finds that perceived usefulness is significantly associated with trust. Nguyen & Ha (2021) study stated that trust is one most important factors influencing e-commerce use.…”
Section: Discussionmentioning
confidence: 95%
“…While user adaptation has been considered as a post-adoptive behavior promoting extended use, continued use and satisfaction (Bala & Venkatesh, 2016;Bhattacherjee & Barfar, 2011), little research has been conducted to date on the relationship between usage-satisfaction (e.g., Aldholay et al, 2018;Isaac et al, 2017Isaac et al, , 2019. Furthermore, although the relationships between behavioral adaptation, user satisfaction and continuance intention have also been proposed (Barki et al, 2007;Bhattacherjee & Barfar, 2011), prior studies on digital platform service systems have rarely investigated the interrelationships between adaptation, CI and satisfaction (Faber & de Reuver, 2019;Franque et al, 2020;Nguyen & Ha, 2021), these links between the three constructs are yet to be confirmed in the ride-hailing service settings. In a RHDP context, the more users perform the adaptation process (i.e., learning how to use platform services or adjusting the platform features accordingly on a smartphone, etc.…”
Section: Continuance Intention (Ci) and Satisfaction (Sa)mentioning
confidence: 99%